PENERAPAN AUTOREGRESSIVE DISTRIBUTED LAG DALAM MEMODELKAN PENGARUH INFLASI, PERTUMBUHAN EKONOMI, DAN FDI TERHADAP PENGANGGURAN DI INDONESIA - Jumhur, Jumhur (Fakultas Ekonomi dan Bisnis, UNTAN, 2020)
This study aims to examine the effect of inflation, economic growth, and foreign investment on unemployment in Indonesia. Using the autoregressive distributed lag (ARDL) analysis method to analyze the 1991-2018 time series data collected from the World Bank's World Development Indicators database. The results found that inflation has a negative and significant effect in the short term but not significant in the long term in Indonesia. Economic growth has a negative and significant effect on both short and long-term unemployment in Indonesia, and foreign investment has a negative and significant effect on both short and long-term unemployment in Indonesia. Through the ARDL model, this research is able to prove that inflation, economic growth, foreign investment, and budgeting are proven to have long-term cointegration or move together in the long term. The four variables also have a dynamic short-term relationship that has a fairly high speed of adjustment towards equilibrium per year. Based on the results, policymakers, in this case the government must provide a conducive investment environment by eliminating the structural rigidity that exists in the economy to attract investment, both foreign and domestic investment, to encourage economic growth and create jobs in Indonesia.